The validity and reliability of the Pressure Ulcer Quality of Life instrument: A methodological study - Gül, Şenay; Avşar, Pınar; Karadağ, Ayişe; Karaçay, Pelin; Gökmen, Derya (Journal of tissue viability, 2023)
This study aimed to adapt the Pressure Ulcer Quality of Life instrument to Turkish and to determine the validity and reliability by using the Rasch model. This methodological study used forward translation, expert opinion, back translation, pilot testing, and finalization for the language adaptation of the instrument. Prior to back translation, the instrument was assessed by five experts certified in wound care nursing. Then, the comprehensibility of the instrument was tested in the pilot study. The study was conducted between March 2017 and September 2019 at one private, one state, and four university hospitals in Turkey. Eligible participants were patients 18 years of age or older, having pressure injury, and fully conscious. Data were collected from a total of 250 patients by using a demographic and clinical history form, the Pressure Ulcer Quality of Life instrument, and the World Health Organization Quality of Life - Brief Form Turkish scale. The instrument's internal construct validity using the Rasch model, the external construct validity, internal consistency, and test-retest reliability were assessed. The final Turkish version of the Pressure Ulcer Quality of Life self-report instrument differed from the original, comprising 74 items under the following ten subscales: three regarding symptoms, plus one itchiness item; four regarding physical functioning; two regarding psychological well-being, self-consciousness, and appearance; and one regarding social participation. The Turkish version of the PU-QOL is a valid, reliable, and widely available instrument for measuring quality of life for patients with pressure injury. •Pressure injury is widely seen and is an important health problem in all individuals with acute or chronic disease.•Valid and reliable instruments are needed to measure the quality of life of patients with pressure injury.•The Turkish version of the Pressure Ulcer Quality of Life scale is a valid and reliable tool for measuring quality of life for patients with pressure injury.•The Turkish version of the Pressure Ulcer Quality of Life scale is recommended to be used to evaluate the quality of life of Turkish-speaking patients with pressure injury in inpatient services, hospices, and home care both in Turkey and worldwide.